First microsecond velocity-space resolved simultaneous measurements of co- and counter-current fast-ion losses in forward and reverse magnetic field in a tokamak - J. Poley-Sanjuán; A. Clément; A. Fasoli; A.N. Karpushov; A. Jansen Van Vuuren; B.P. Duval; J. Ayllon-Guerola; M. Garcia-Munoz; M. Toussaint; M. Vallar; P. Lavanchy; Y. Andrebe; et al. (Nuclear Fusion)
A novel Fast Ion Loss Detector was designed, manufactured, installed and commissioned at the Tokamak á Configuration Variable. This is the first Fast Ion Loss Detector to feature four collimators that enable simultaneous detection of co- and counter-current fast-ion losses for reversed and forward magnetic fields. The detector is, thus, sensitive to all magnetic field scenarios and simultaneously to positively and negatively charged particles across the complete range of operational conditions. The diagnostic is equipped with a dual-camera system: a complementary metal oxide semiconductor (CMOS) offering high-spatial resolution with medium-temporal resolution (up to ∼3.6 kHz frame rate) with a second, discrete chord camera, providing medium-spatial resolution with high temporal resolution (up to four MHz bandwidth). Together with a fast scintillator, the fast camera system (made of 128 avalanche photodiodes) allows velocity-space resolved measurements of fast-ion losses that retain the signal frequency characteristics. The detector’s energy-pitch sensitivity starts from ∼5 keV in energy, E , with up to ∼0.95 in pitch, $λ = v_\parallel/v$ . It was commissioned across all four possible configurations of magnetic field and plasma current polarities. The fast avalanche photodiodes signal was velocity-space mapped with a good agreement to the high-resolution CMOS camera, but now features µ s temporal resolution. The scintillator emission was mapped to velocity-space, showing a clear match between both the CMOS and the fast camera while retaining the frequency characteristics, which, for one of the discharges, include a sawtooth mode.